Surgical Treatment of the Cleft Foot: A Case Report - Karakurt, Lokman; Köse, Rüştü (Fırat University, 2001)
Cleft foot is a rare congenital deformity. Cleft foot is usually bilateral and associated with other congenital deformities such as cleft hand, cleft plate and cleft lip. Usually, surgical treatment is preferred and recommended before one-year old. Good result is expected by evaluation of foot function, roentgenogram and cosmesis. The aim of this study is discussion a case with cleft foot. We operated on a 10 year-old boy with bilateral cleft foot, capsulotomy was performed and syndactylism was created. At 22th month postoperatively, cosmetic, radiologic and functional results was good.

Konjenital yarık-ayak deformitesi nadir görülmektedir. Bu deformite genelde bilateraldir ve başka anomalilerle birlikte bulunabilmektedir. Tedavide fonksiyonel, röntgenografik ve kozmetik yönden tatmin edici sonuç alınmaya çalışılır. Biz konjenital yarık-el / yarık-ayak deformitesi nedeniyle ameliyat ettiğimiz bir olgumuzu tartışmayı amaçladık. Bilateral yarık-el / yarık-ayak anomalisi olan 10 yaşında erkek hastanın ayak deformitelerine cerrahi teknik olarak kapsülotomi, k- teli ile tespit ve sindaktilizm yaptık. Tedavi sonrası 22 aylık takibimizde fonksiyonel, kozmetik ve radyolojik sonucumuz tatmin ediciydi.
YARIK AYAK DEFORMİTESİNİN CERRAHİ TEDAVİSİ: OLGU SUNUMU